STRUKTUR KALIMAT BAHASA ARAB DAN BAHASA PERSIA - Siti Fatimah; M. Agus Budianto (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2020)
This paper describes the differences between Arabic and Persian sentence structure to help beginner Persian learners, especially those with Arabic language knowledge. This is a library research using linguistic approach and contrastive analysis to compare both sentence structre to predict difficulties that might appear in learning Persian. The differences of both languages, i.e. : 1) there ara two formulas of Arabic sentence structure: a) subject + predicate, and b) predicate + subject or predicate + subject + object. While in Persian the formula is subject + predicate or subject + object + predicate; 2) negative sentences of both languages use negative particle, but Arabic has various ones and most of them change the i‟rab; 3) Arabic passive sentences follows the wazn ل ِ ُع ف) past) and ُ ل ْع ف ُ يػ) present), while in Persian uses ending of شدن after the past verbs; 4) Arabic imperatives are formed by adding hamzah wasal replacing the huruf mudara‟ah, while in Persian by adding بــ before the root of present verbs; 5) fi‟l nahyi in Arabic are formed by adding lam an-nahiyah before majzum present verbs, while in Persian by adding نــ before root of present verbs.